An Identification of Efficient Cropping Zone for Cotton in Tamil Nadu - Rathika, K.; Sasikumar, K. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted at Agro Climate Research Centre, Coimbatore, Tamil Nadu during the year 2025 to identify efficient cropping zones for cotton in Tamil Nadu state, India. The district wise data on area, production and productivity of cotton for the period 1985 to 2024 were collected from the Department of Statistics in Tamil Nadu and and the Indiastat database. The relative spread index (RSI) and relative yield index (RYI) were computed and the potential cropping districts for cotton were identified. The results revealed that the RSI was maximum in Virudhunagar district (559.7), followed by Perambalur (386.0), Madurai (290.3), Ariyalur (289.1), Thoothukudi (288.4) and Thirunelveli (205.1). The relative yield index was maximum in Thiruppur district (163.7) followed by Theni (150.1), Krishnagiri (147.5) and Namakkal (138.7). Based on RSI and RYI indices Ariyalur, Dharmapuri, Coimbatore, Salem, Theni, Thirunelveli and Tenkasi were identified as the Most Efficient Cropping Zones. Conversely, Thiruchirappalli, Madurai, Virudhunagar, Perambalur and Thoothukudi were classified as area efficient cropping zones; in these regions, the cultivated area was significantly high, yet productivity remained low, suggesting a critical need for farmer training in innovative technologies. Furthermore, Tiruvallur, Ramanathapuram, The Nilgiris and Kanyakumari were categorized as non-efficient cropping zones, while the remaining 16 districts were identified as yield-efficient cropping zones. Decadal relative spread index (DRSI) and relative yield index (DRYI) analyses (1985–2024) revealed widening spatial divergence. Highly stable rainfall in Kancheepuram supported the highest productivity (DRYI 201.0), whereas extreme variability in Perambalur (RSI 724.3) and Ramanathapuram led to regressive yield trends.